Faith and Knowledge Begin at Home: The Mother as the First Educator in the Religious and Secular Development of the Christian Child - Janet Solomon (Darul Yasin Al Sys, 2026)
The Christian home serves as the first school where faith and knowledge are simultaneously nurtured. This paper examines the pivotal role of mothers as the first educators in the moral, religious, and secular development of children. Using biblical examples such as Jochebed, Hannah, Mary, Lois, and Eunice, the study highlights how maternal faith, prayer, and intellectual engagement shape both the spiritual and academic growth of Christian children. Drawing from Bandura’s Social Learning Theory and Bronfenbrenner’s Ecological Systems Theory, the study underscores that children learn values, discipline, and intellectual curiosity through their mothers’ modelling and home environment. However, the research identifies contemporary challenges, including busy schedules, moral apathy, and illiteracy—that hinder mothers from fulfilling this divine responsibility. It concludes that mothers remain indispensable in balancing religious and secular education, ensuring that faith and knowledge develop harmoniously at home for the holistic growth of the child and society.